PENGEMBANGAN WISATA MATA AIR MEDJET DI DESA SELELOS KECEMATAMAN GANGGA KABUPATEN LOMBOK UTARA - Apriliana, Rizky Ayu; Scabra, Andre Rachmat; Madaniyah, Syifa; Fidhun, Muhammad; Pratama, Agus Irawan (Universitas Mataram, 2024)
Selelos Village is a village in North Lombok Regency, Gangga District which has potential natural resources such as agro potential with abundant plantation products, natural potential with waterfall and spring tourism as well as very historical, cultural and local wisdom potential. large. One of the natural potentials for water tourism in Selelos village is the Kakong Springs Tourism or also known as the Medjet Springs. The aim of the UNRAM KKN-PMD activities in Selelos Village is to try to re-optimize the management of Medjet Spring tourism so that it can attract more tourists through the Selelos Village Medjet Spring Tourism Development work program. The method of implementing the activities carried out is a participatory method by collaborating with Pokdarwis, KUN and Karang Taruna Selelos Village. The results of this activity are useful for preserving springs in efforts to restore the environment for the community, increasing visitor attraction, maintaining the safety and comfort of tourist attractions, as well as a sustainable living environment.